Meningkatkan Kepercayaan Diri Remaja Akhir Melalui Dukungan Emosional Pengasuh di Panti Sosial Bina Remaja Taruna Jaya 1 - Radysti Devania; Muhammad Sahrul (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Every teenager needs something called self-confidence because self-confidence plays an important role in developing personality and skills to become better. Problems that affect the self-confidence of teenagers living in social institutions include teenagers who have an inferior and shy attitude when appearing in public, often isolate themselves, do not focus on studying, and are reluctant to express their opinions. This can cause teenagers to regret the situation. The purpose of this study was to determine and describe how emotional support from caregivers increases the self-confidence of late adolescents, and to identify the supporting and inhibiting factors in providing emotional support from caregivers to late adolescents. This research method uses a qualitative approach with data obtained from observations, interviews, and documentation. The results of the study show that emotional support provided by caregivers, seen through consistent empathy, sincere concern, responsive attention, and appreciation through praise, increases the self-confidence and motivation of adolescents. Encouragement for active participation and responsibility also helps adolescents overcome fears and develop their potential. Supporting factors include adolescents' openness to advice, while rejection of help is an inhibiting factor. Case studies show that emotional support and positive social interactions significantly increase self-confidence, with positive changes observed in late adolescents at the Taruna Jaya 1 social care center for adolescents.